Presupposition Triggers in Editorials of the Jakarta Post - Eka Surya Fitriani; Sri Minda Murni (LINGUISTIK TERAPAN, 2016)
The objectives of the study were to find out: (1) the realization of presupposition triggers in editorials of The Jakarta Post (2) the reasons for using presupposition triggers. The study was descriptive qualitative. The source of data was The Jakarta Post online website. The data of the study were the sentences or clause which triggered the presupposed meaning in editorials. The data were identified, analyzed, and categorized based on Levinson’s theory. The findings of the study showed that: (1) 12 from 13 presupposition triggers were found namely: definite description, factive verb, implicative verb, change of state verbs, judging verbs, iterative item, cleft sentences, questions, temporal clause, comparison clause, counterfactual conditional sentence and non-restrictive relative clause, while implicit cleft with stressed constituents was not found. (2) The reasons were a) commonly to present the background information which is assumed to be true, b) to recall the readers toward the information of the event that they have not unintentionally acknowledged, c) to interpret the editorialists’ attitude on the fact of the event and d) to awaken the readers’ curiosity to the questioning things.   Keywords: Editorials, Presupposition Triggers, Levinson theory.